Food insecurity among postsecondary students in developed countries: A narrative review. Issue 11 (5th November 2018) - Lee, Sarah Dawn; Hanbazaza, Mahitab; Ball, Geoff D.C.; Farmer, Anna; Maximova, Katerina; Willows, Noreen D.
Abstract : Purpose: The purpose of this paper is to conduct a narrative review of the food insecurity literature pertaining to university and college students studying in Very High Human Development Index countries. It aims to document food insecurity prevalence, risk factors for and consequences of food insecurity and food insecurity coping strategies among students. Design/methodology/approach: English articles published between January 2000 and November 2017 were identified using electronic databases. Quality Assessment Tool for Quantitative Studies assessed the study quality of quantitative research. Findings: A total of 37 quantitative, three mixed-methods and three qualitative studies were included from 80, 914 students from the USA ( n =30 studies), Australia ( n =4), Canada ( n =8) and Poland ( n =1). Prevalence estimates of food insecurity were 9–89 percent. All quantitative studies were rated weak based on the quality assessment. Risk factors for food insecurity included being low income, living away from home or being an ethnic minority. Negative consequences of food insecurity were reported, including reduced academic performance and poor diet quality. Strategies to mitigate food insecurity were numerous, including accessing food charities, buying cheaper food and borrowing resources from friends or relatives. Research limitations/implications: Given the heterogeneity across studies, a precise estimate of the prevalence of food insecurity in postsecondary students is unknown. Practical implications: For many students studying in wealthy countries, obtaining a postsecondary education might mean enduring years of food insecurity and consequently, suffering a range of negative academic, nutritional and health outcomes. There is a need to quantify the magnitude of food insecurity in postsecondary students, to inform the development, implementation and evaluation of strategies to reduce the impact of food insecurity on campus. Originality/value: This review brings together the existing literature on food insecurity among postsecondary students studying in wealthy countries to allow a better understanding of the condition in this understudied group.